Standard Operating Procedure (SOP) for mould room practices and simulation of head neck cancer patients undergoing proton therapy. (December 2022) - Gaikwad, Utpal; Mookaiah, Minnal; Karthekeyan, S.; Wakde, Manoj; Noufal, M.P.; Chilukuri, Srinivas; Sharma, Dayananda; Jalali, Rakesh; Nangia, Sapna
Highlights: Critical role of immobilization and simulation in head neck cancer patients undergoing radiation therapy. Special requirements of proton HN immobilization and simulation. Details of immobilization materials/equipment used for HN immobilization. Detailed steps of all mould room procedures for HN proton patients. Abstract: Head Neck cancer patients treated with modern proton therapy need special attention during mould room procedures. In addition to usual mould room practices, patients undergoing Intensity Modulated Proton Therapy (IMPT) require attention to the special characteristics of protons viz., sensitivity to beam path and its alteration, sharp dose fall off and end of range. In this article, we discuss the Standard Operating Procedure (SOP) for HNC immobilization and simulation for IMPT, developed and practiced at our centre. The SOP details each step during the immobilization and simulation process, with nuances specific to IMPT.